Meta-Analysis of the Relationship Between Mathematics Learning and Cooperative Learning Models with the Object of Elementary School Students - Dema Yulianto; Nur Ainun; Emy Yunita Rahma Pratiwi; Isfauzi Hadi Nugroho; Naila Fikrina Afrih Lia (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
The purpose of this research is to determine the impact of the cooperative learning model on elementary school students' mathematics learning. Meta-analysis is the technique employed. The elementary school sample study, which covered experimental work using cooperative learning methods in math instruction, covered a range of 18 students. A coding sheet that compiles data and journal entries serves as the instrument in use. The average value of the effect, 0.39, falls into the large effect group according to an analysis of the overall effect's magnitude. The analysis's conclusions also demonstrate that the cooperative learning approach has an impact on math instruction at the primary school level.